Uma metodologia automatizada por fluxo-batelada para a preparação de microemulsões de gasolina e de nafta para a determinação de íons metálicos por espectrometria de absorção atômica em forno de grafite - Cunha, Francisco Antonio da Silva (2011)
In this work we have developed an automated methodology for the analysis of metals in gasoline and naphtha in the form of microemulsions using a flow-batch analyzer with piston propulsion for the preparation of microemulsions and quantification of analytes by GF AAS. Three studies were conducted, the first concerning the study of optimal composition of microemulsions made through the construction of phase diagrams for gasoline and naphtha. The second study sought to improve all operational parameters of the automatic system for the production of solutions and also in relation to their coupling to the instrument for analysis. Finally it was done to optimize the operating parameters of the GF AAS for the quantification of metals which have been quantized in two ways, the first quantification by a procedure manual preparation of microemulsions and the second by the same automatic preparation. The two results were then compared by paired t test at a 95% level of confidence, no significant differences between the two relevant procedures. Furthermore, recovery tests performed showed acceptable accuracy for the two methods investigated, with average recoveries in the ranges from 88 to 93% for the automatic method and between 86 to 92% without significant differences in both a 95% level of confidence. The characteristic masses obtained were 0.36pg for Cu, 0.29pg for Cr and 0.87pg for Pb, with limits of detection and quantification respectively of 0.073 and 0.22 for Cu, 0.024 and 0.72 for Cr and 0.115 and 0.346 for Pb.